Pengaruh Kualitas Panggilan Seluler dan Nilai Ekonomis terhadap Loyalitas Pelanggan dengan Kepuasan Pelanggan Sebagai Mediasi (Studi pada Pembelian Produk Telkomsel Prabayar Simpati di Pontianak) - Saputra, Egi; Ramadania, Ramadania; Heriyadi, Heriyadi; Pebrianti, Wenny (Primary Journal of Multidisciplinary Research, 2025)
Telkomsel is recognized as a leading telecommunications network in Indonesia. However, some customers continue to express concerns about network quality not always meeting expectations and service rates perceived as relatively high. As one of the largest transmission service providers in Indonesia, Telkomsel serves a customer base of approximately 169.2 million. The company offers a prepaid starter card, Simpati, designed to meet various user needs. This study aims to analyze the influence of Mobile Call Quality and Value for Money on Customer Satisfaction and its impact on Customer Loyalty among Simpati users. The research is motivated by the importance of service quality and perceived value in maintaining customer satisfaction and loyalty in the highly competitive telecommunications industry. Data were collected from 200 respondents who are active Telkomsel prepaid users, specifically of the Simpati product, using purposive sampling. Data analysis was conducted using SmartPLS 4 software with a Structural Equation Modeling (SEM) approach based on Partial Least Squares. The results show that both Mobile Call Quality and Value for Money significantly influence Customer Satisfaction, which in turn positively affects Customer Loyalty. These findings offer strategic implications for Telkomsel, particularly regarding the Simpati product, in managing service quality and perceived value to retain long-term customers.